Temporal Trends of Functional Outcome in Patients With Acute Ischemic Stroke Treated With Intravenous Thrombolysis. Issue 11 (24th August 2022) - Marko, Martha; Miksova, Dominika; Ebner, Johanna; Lang, Marie; Serles, Wolfgang; Sommer, Peter; Sykora, Marek; Lang, Wilfried; Knoflach, Michael; Kiechl, Stefan; Greisenegger, Stefan
Abstract : Background: Intravenous thrombolysis improves functional outcome in patients with acute stroke and frequencies of r-tPA (recombinant tissue-type plasminogen activator) treatment have been increasing over time. We aimed to assess whether functional outcome in r-tPA–treated patients improved over time and to investigate the influence of clinical variables on functional outcome. Methods: We analyzed data of r-tPA–treated patients in the Austrian Stroke Unit Registry from 2006 to 2019. Favorable functional outcome was defined as modified Rankin Scale score of 0 to 2. Frequencies of modified Rankin Scale score of 0 to 2 were assessed for the overall population and in prespecified subgroups; multivariable logistic regression analysis was performed to assess associations of baseline characteristics including clinically relevant interactions, and outcome. Results: Overall, 4865 out of 9409 r-tPA–treated patients (51.7%) achieved favorable functional outcome 3 months post stroke. Between 2006 and 2019, frequencies of favorable functional outcome increased from 45.9% to 56.8%. In multivariable logistic regression analysis, year of treatment (adjusted odds ratio [adjOR], 1.08 [95% CI, 1.01–1.15]) was associated with favorable functional outcome. Stroke severity (National Institutes of Health Stroke Scale, adjOR, 0.86 [95% CI, 0.85–0.87]), age (61–70 years: adjOR, 0.67 [95% CI, 0.55–0.80], 71–80 years: adjOR, 0.42 [95% CI, 0.35–0.50], >80 years: adjOR, 0.16 [95% CI, 0.13–0.20]), female sex (adjOR, 0.89 [95% CI, 0.79–0.99]), and various comorbidities (eg, atrial fibrillation, prior stroke, diabetes) were negatively associated. Inclusion of interaction terms into the multivariable logistic regression model suggests a positive effect of year of treatment and endovascular treatment by increasing stroke severity on functional outcome (interaction between year of treatment and National Institutes of Health Stroke Scale: adjOR, 1.01 [95% CI, 1.00–1.02], interaction between National Institutes of Health Stroke Scale and endovascular treatment: adjOR, 1.02 [95% CI, 1.01–1.03]). Conclusions: Frequencies of favorable functional outcome in r-tPA–treated patients have been increasing over time, likely driven by improved outcome in patients with more severe strokes receiving endovascular treatment. However, some subgroups are still less likely to achieve functional independency and deserve particular attention.